2022
DOI: 10.3389/fimmu.2022.933973
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel cuproptosis-related gene signature and integrative analyses in patients with lower-grade gliomas

Abstract: BackgroundCuproptosis is a newly discovered unique non-apoptotic programmed cell death distinguished from known death mechanisms like ferroptosis, pyroptosis, and necroptosis. However, the prognostic value of cuproptosis and the correlation between cuproptosis and the tumor microenvironment (TME) in lower-grade gliomas (LGGs) remain unknown.MethodsIn this study, we systematically investigated the genetic and transcriptional variation, prognostic value, and expression patterns of cuproptosis-related genes (CRGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 92 publications
(90 reference statements)
1
35
0
Order By: Relevance
“…Dihydrolipoamide Branched Chain Transacylase E2(DBT) catalyzed α-keto acid to acyl-CoA, which is thought to be associated with protective effects in both LUAD and cervical cancer(CC) patients [ 159 , 164 ]. Cytochrome c oxidase assembly factor 19(COX19) was involved in SCO1-dependent signaling essential for copper homeostasis [ 185 ], which was thought to be a risk factor in both gliomas and low-grade gliomas [ 140 , 142 ]. Pituitary tumor-transforming gene 1 protein(PTTG1), a key regulator of the p53/TP53 pathway and DNA repair, has been considered as a risk factor in studies of HCC by different investigators [ 133 , 135 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dihydrolipoamide Branched Chain Transacylase E2(DBT) catalyzed α-keto acid to acyl-CoA, which is thought to be associated with protective effects in both LUAD and cervical cancer(CC) patients [ 159 , 164 ]. Cytochrome c oxidase assembly factor 19(COX19) was involved in SCO1-dependent signaling essential for copper homeostasis [ 185 ], which was thought to be a risk factor in both gliomas and low-grade gliomas [ 140 , 142 ]. Pituitary tumor-transforming gene 1 protein(PTTG1), a key regulator of the p53/TP53 pathway and DNA repair, has been considered as a risk factor in studies of HCC by different investigators [ 133 , 135 ].…”
Section: Introductionmentioning
confidence: 99%
“…The expression matrix of BPD disease genes was obtained using perl language script, and the expression of copper death genes in the matrix was extracted from the corrected data to obtain the expression matrix of 19 CRGs (Bao et al, 2022). Based on the CRGs expression matrix, the "limma" package (Ritchie et al, 2015) was used to analyze the correlation between differential expression and CRGs between the experimental and control groups.…”
Section: Expression Of Crgsmentioning
confidence: 99%
“…Iron-sulfur cluster proteins play a key role in cuproptosis and their homeostasis is involved in cuproptosis-dependent cancer therapy. Several recent studies have shown that cuproptosis-associated genes, including iron-sulfur clusters, are potential predictors of diagnostic, prognostic, and therapeutic response in some cancers and are associated with tumor microenvironment, immune response and immunotherapy [143][144][145][146][147].…”
Section: Iron-sulfur Clusters and Cuproptosismentioning
confidence: 99%